Molecular biomarkers in metastatic clear cell renal cell carcinoma treated with first-line immune combinations: a systematic review of phase III randomized clinical trials by Meet-URO group - Anna Amela Valsecchi; Michele Maffezzoli; Maria Concetta Cursano; Fabrizio Di Costanzo; Andrea Malgeri; Mattia Alberto Di Civita; Brigida Maiorano; Carlo Messina; Giuseppe Procopio; Davide Bimbatti; Sebastiano Buti; Sara Elena Rebuzzi; et al. (Cancer and Metastasis Reviews, 2026)
Immune checkpoint inhibitor (ICI)–based combinations represent the standard first-line treatment for metastatic clear cell renal cell carcinoma (mRCC), although robust biomarkers for treatment selection remain undefined. We conducted a systematic review to identify biomarkers assessed in randomized clinical trials (RCTs) on first-line ICI-based regimens. Following PRISMA guidelines, we searched PubMed, Web of Science and Scopus (January 2018–October 2025) for phase III RCTs investigating first-line ICI-based therapies in mRCC with molecular or circulating biomarker analyses. Given heterogeneity across studies, a qualitative synthesis was performed. Sixteen reports were included. Biomarkers were assessed using immunohistochemistry, transcriptomics, genomic sequencing and blood analyses. PD-L1 expression did not reliably discriminate benefit across ICI-based combinations, although it revealed a negative prognostic influence with sunitinib and a potential predictive role for nivolumab-ipilimumab. Tumours with angiogenic signatures were consistently associated with improved outcomes, suggesting prognostic relevance, while derived limited additional benefit from ICIs. Immune-related signatures were associated with ICI response, whereas proliferation and MYC -related signatures identified disease with poor prognosis across treatments. Individual mutations (e.g. PBRM1 , VHL , BAP1 , PTEN ) showed heterogeneous and mainly prognostic associations, whereas composite gene panels (e.g. rDM) may offer better predictive value. Circulating biomarkers, including inflammatory cytokines and KIM-1 dynamics, demonstrated promising prognostic and early predictive signals. No validated biomarker currently supports treatment selection among first-line ICI-based combinations in mRCC. Future research should prioritize adaptive, biomarker-guided trial designs integrating longitudinal multi-omic profiling and circulating biomarkers to generate clinical evidence and support personalized treatments.

Time to metastasis as a prognostic factor in metastatic urothelial carcinoma: results from the ARON-2 study - Renate Pichler; Gerald Klinglmair; Kirstin Binz; Enrique Grande; Alina Pirshtuk; Hideki Takeshita; Yüksel Ürün; Javier Molina-Cerrillo; Zin W. Myint; Alfonso Gómez de Liaño; Augusto Mota; Alessia Salfi; et al. (Clinical & Experimental Metastasis, 2025)

Prognostic immunotherapy score (PIS) in patients with advanced urothelial carcinoma treated with pembrolizumab: real-world data and validation from ARON-2 dataset - Alessandro Rizzo; Anas Zayed; Elsa Vitale; Sebastiano Buti; Hideki Takeshita; Simon Crabb; Giandomenico Roviello; Emmanuel Seront; Jose Carlos Tapia; Sarah Scagliarini; Lazar Popovic; Ray Manneh Kopp; et al. (Clinical & Experimental Metastasis, 2025)

Concomitant medications in patients with metastatic urothelial carcinoma receiving enfortumab vedotin: real-world data from the ARON-2EV study - Ondřej Fiala; Sebastiano Buti; Kazutoshi Fujita; Alfonso Gómez de Liaño; Wataru Fukuokaya; Takahiro Kimura; Takafumi Yanagisawa; Patrizia Giannatempo; Martin Angel; Alessia Mennitto; Javier Molina-Cerrillo; Maria T. Bourlon; et al. (Clinical & Experimental Metastasis, 2025)
Patients with metastatic urothelial carcinoma (mUC) are typically elderly and often have other comorbidities that require the use of concomitant medications. In our study we evaluated the association of concomitant use of antibiotics (ATBs), proton pump inhibitors (PPIs), corticosteroids, statins, metformin and insulin with patient outcomes and we validated the prognostic role of a concomitant drug score in mUC patients treated with enfortumab vedotin (EV) monotherapy. Data from 436 patients enrolled in the ARON-2 EV retrospective study were analyzed according to the concomitant medications used at baseline. Finally, the patients were stratified into three risk groups according to the concomitant drug score based on ATBs, corticosteroids and PPIs. Statistical analysis involved Fisher exact test, Kaplan–Meier method, log-rank test, and univariate/multivariate Cox proportional hazard regression models. Inferior survival outcomes were observed in ATB users compared to non-users (OS: 7.3 months, 95%CI 5.0 − 12.3 vs 13.7 months, 95%CI 12.2 − 47.3, p = 0.001; PFS: 5.1 months 95%CI 3.3 − 17.7 vs 8.3 months, 95%CI 7.1 − 47.3, p = 0.001) and also in corticosteroid users compared to non-users (OS: 8.4 months, 95%CI 6.6 − 10.0 vs 14.2 months, 95%CI 12.7 − 47.3, p < 0.001; PFS: 6.0 months 95%CI 4.6 − 7.9 vs 8.9 months, 95%CI 7.2 − 47.3, p = 0.004). In the Cox multivariate analysis, the concomitant drug score was a significant factor predicting both OS (HR = 1.32 [95% CI 1.03 − 1.68], p = 0.026) and PFS (HR = 1.23 [95% CI 1.01 − 1.51], p = 0.044). Our findings suggest detrimental impact of concomitant use of ATBs and corticosteroids on survival outcomes and the prognostic utility of the concomitant drug score in previously treated mUC patients receiving EV.

Pembrolizumab in patients with advanced upper tract urothelial carcinoma: a real-world study from ARON-2 project - Alessandro Rizzo; Sebastiano Buti; Patrizia Giannatempo; Samer Salah; Javier Molina-Cerrillo; Francesco Massari; Ray Manneh Kopp; Ondřej Fiala; Luca Galli; Zin W. Myint; Deniz Tural; Andrey Soares; et al. (Clinical & Experimental Metastasis, 2024)

External validation of a red cell-based blood prognostic score in patients with metastatic renal cell carcinoma treated with first-line immunotherapy combinations - Michele Maffezzoli; Matteo Santoni; Giulia Mazzaschi; Sara Rodella; Eleonora Lai; Marco Maruzzo; Umberto Basso; Davide Bimbatti; Roberto Iacovelli; Annunziato Anghelone; Ondřej Fiala; Sara Elena Rebuzzi; et al. (Clinical & Experimental Metastasis, 2024)
Immunotherapy combinations with tyrosine-kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) had significantly improved outcomes of patients with mRCC. Predictive and prognostic factors are crucial to improve patients’ counseling and management. The present study aimed to externally validate the prognostic value of a previously developed red cell-based score , including hemoglobin (Hb), mean corpuscular volume (MCV) and red cell distribution width (RDW), in patients with mRCC treated with first-line immunotherapy combinations (TKI plus ICI or ICI plus ICI). We performed a sub-analysis of a multicentre retrospective observational study (ARON-1 project) involving patients with mRCC treated with first-line immunotherapy combinations. Uni- and multivariable Cox regression models were used to assess the correlation between the red cell-based score and progression-free survival (PFS), and overall survival (OS). Logistic regression were used to estimate the correlation between the score and the objective response rate (ORR). The prognostic impact of the red cell-based score on PFS and OS was confirmed in the whole population regardless of the immunotherapy combination used [median PFS (mPFS): 17.4 vs 8.2 months, HR 0.66, 95% CI 0.47–0.94; median OS (mOS): 42.0 vs 17.3 months, HR 0.60, 95% CI 0.39–0.92; p < 0.001 for both]. We validated the prognostic significance of the red cell-based score in patients with mRCC treated with first-line immunotherapy combinations. The score is easy to use in daily clinical practice and it might improve patient counselling.